2020
DOI: 10.3390/ijerph17166008
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Competence Mediates the Relationship between Communication Problems and Reactive Externalizing Problems in Children with and without Developmental Language Disorder: A Longitudinal Study

Abstract: Language problems are a risk factor for externalizing problems, but the developmental path remains unclear. Emotional competence may mediate the relationship, especially when externalizing problems are reactive in nature, such as in Oppositional Deviant Disorder (ODD) and reactive aggression. We examined the development of reactive and proactive externalizing problems in children with (n = 98) and without (n = 156) Developmental Language Disorder (DLD; age: 8–16 years) over 18 months. Relationships with commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 65 publications
3
20
0
2
Order By: Relevance
“…For example, the stress of coping with DLD may exacerbate genetic influences on internalizing problems (i.e., DLD moderates genetic risk for internalizing problems). This is consistent with evidence that childhood stressful experiences increase susceptibility to genetic risk for emotional problems such as depression (Uher, 2014). This possibility, however, needs to be specifically investigated, for example using genomic methods.…”
Section: Quantitative Differences In Etiological Influences Between Groupssupporting
confidence: 86%
See 2 more Smart Citations
“…For example, the stress of coping with DLD may exacerbate genetic influences on internalizing problems (i.e., DLD moderates genetic risk for internalizing problems). This is consistent with evidence that childhood stressful experiences increase susceptibility to genetic risk for emotional problems such as depression (Uher, 2014). This possibility, however, needs to be specifically investigated, for example using genomic methods.…”
Section: Quantitative Differences In Etiological Influences Between Groupssupporting
confidence: 86%
“…An alternative explanation for the etiological association between DLD and psychopathology in young people is that genetic and/or environmental influences on psychopathology are stronger in the presence of DLD. For example, DLD may create a stressful environment, which can potentiate genetic influences on psychopathology as captured by the diathesis-stress framework (Manuck & McCaffery, 2014;Uher, 2014); however, this possibility has not been previously investigated.…”
Section: Behavioral Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically developing children were recruited via mainstream schools. This sample formed part of an ongoing programme of research and has been reported on in previous publications [18,20,[24][25][26].…”
Section: Participantsmentioning
confidence: 99%
“…This can ensure that the behaviors do not persist, which is important, as children whose behavior problems are not addressed early are at risk for a host of adverse health, educational, relational, and psycho-social outcomes (D'Amico et al, 2014;Maughan et al, 2013). Children with behavior problems tend to have problems with emotional competence; meaning that their knowledge of emotions, and skills with regard to regulating them is compromised (van den Bedem et al, 2020). As such, targeting children's emotional competence through emotionfocused interventions can assist with ameliorating behavior problems (Havighurst et al, 2014).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%